Compreensão de tirinhas da Mafalda em enunciados de questões de prova - Camila Engler Barbosa (2015)
This research aims to verify how the wordings of the questions in the tests help the students to understand texts in which pictures and words are associated, specifically in Mafaldas comic strips that serve as motivation for we understand the function of texts that combine pictures and words. We try to comprehend why do students have some rejection about Quinos character? Why do they call her as The evil? Do they know how to read these comic strips? The hypothesis we thought to reply to those questions is that Mafalda is known as The evil because Quinos texts and also other authors texts are used on tests in which the wordings of the questions are too complicated and, therefore, they do not help the students to understand the content of the text. To verify that hypothesis, we have carried out a qualitative and quantitative research that has as its corpus Portuguese Language test questions, in the second elementary school cycle, applied to students of 6º to 9º levels of a particularly school of Belo Horizonte, during the year of 2011 and 2014. For we obtain the answer that we aim about the rejection of Mafalda we search to know what are the genre and the texts those combine verbal and non-verbal are present in the tests, how are these texts worked, what kind of questions mobilize and whither these questions help the students to comprehend these texts, that may be a Mafaldas text or not. The analysis of the corpus is established on socio interacionist theory of language, text, reader and reading process. The main theories are from: Antunes (2010), Brito e Pimenta (2009), Koch (2009), Koch e Elias (2009; 2011), Kress e Van Leeuwen (2001;2006), Marcuschi (2008; 2011) e Moretto (2010). These last two authors, respectively, helped on the analysis of typologies of the questions presented in the tests and in the conceptions about the tests as a tool of evaluation of learning in the school. It were elaborated tables divided by levels (6º a 9º) to quantify texts and genres which were present in the tests and to analyze each one of the corpus questions. The goal of that process is to comprehend which are the abilities required on those test wording questions. Between the most important results of this work, it is the assumption that texts which articulate verbal and non verbal components are used in tests aiming at evaluation of students knowledge, almost exclusively, on traditional grammar. That assumption is more evident in questions in which motivational text is comic strips whether they are Mafalda ones or not. It was possible to verify as well the potential those comic strips have to improve reading comprehension, as they present several multimodal components that can be used in the classroom. Besides that, this research has shown the fact that texts which associate images and with words make up the majority in the analyzed tests, but still the association between verbal and non verbal components has been badly implemented nor even has been mentioned in the question wording. Even though it was not our goal, we noticed that the work with only verbal texts only, featured as a narrative type, do not motivate grammar questions at all, but only questions in which the aim is to verify whether either the student has read the text or not in the case of a paradidactic text either to check text comprehension.